Analysis of Risk Factors for Chronic Kidney Disease in Young Adults at Rasyida Kidney Hospital, Medan, in 2024 - Gultom, Yosephine Octaviana; girsang, Ermi; Mukti, Ade Indra (Syntax Corporation, 2025)
Chronic kidney disease (CKD) is a global health problem with a high economic burden and significant mortality. In Indonesia, the prevalence of CKD continues to rise, while cardiometabolic factors such as hypertension and diabetes, as well as certain infections (e.g., hepatitis B), are thought to contribute to disease progression in young adults. To determine the association between age, sex, hypertension, diabetes mellitus, and hepatitis B with CKD stage, and to identify the most influential factors in young adult patients. This was a retrospective study of medical records from patients aged 19-44 years at Rasyida Kidney Specialty Hospital, Medan, in 2024 (total sampling; n = 121). The dependent variable was CKD stage (stages 4-5). Univariate analysis was performed to describe patient characteristics; bivariate analysis (Fisher’s exact test) was used to assess the association between each factor and CKD stage; and multivariate logistic regression was used to determine independent predictors of advanced CKD. Of the 121 patients, 57% (69) were male, and the majority were aged 33-44 years (62.8%, n = 76). Stage 2 hypertension was present in 55.4% (67) of patients. A history of diabetes was found in 22.3% (27), with 18.2% (22) classified as prediabetic. Hepatitis B was identified in 10.7% (13). Bivariate analysis showed significant associations between CKD stage and hypertension (p < 0.001), diabetes (p < 0.001), and hepatitis B (p = 0.004), but no significant associations for sex (p = 0.052) or age (p > 0.05). Multivariate regression confirmed hypertension (p < 0.001), diabetes (p < 0.001), and hepatitis B (p= 0.033) as independent predictors of advanced CKD. In young adults, CKD stage is strongly associated with hypertension particularly stage 2 as well as diabetes mellitus and hepatitis B, while age and sex show no significant association. These findings highlight the importance of blood pressure screening and control, strict glycemic management, and hepatitis B treatment to slow CKD progression. Further studies are recommended to include lifestyle and metabolic factors such as BMI, dyslipidemia, salt intake, smoking, family history, and treatment adherence.